2022
DOI: 10.11606/s1518-8787.2022056004324
|View full text |Cite
|
Sign up to set email alerts
|

Ambient air pollutants relate to hospital admissions for chronic obstructive pulmonary disease in Ganzhou, China

Abstract: OBJECTIVE To evaluate the relationship between ambient air pollutants and chronic obstructive pulmonary disease in relatively low-polluted areas in China. METHODS Atmospheric pollutants levels and meteorological data were obtained from January 2016 to December 2020. The medical database including daily hospital admissions for chronic obstructive pulmonary disease (ICD10: J44) was derived from the First Affiliated Hospital of Gannan Medical University. The generalized additive model was used to analyze the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Unfortunately, our findings for particulate matter do not align with several previous reports in the literature that have been conducted in some other regional countries or cities [13][14][15][16][17][18][19]. We observed that short-term exposure to PM 2.5 or PM 10 did not correlate significantly with COPD morbidity, which was consistent with findings from Berlin, Germany, and Jinan, China, the authors of the above two articles identified that PM 2.5 and PM 10 were also not found to significantly influence COPD hospitalizations in their study [12,20], while the results of some prior studies in Zhangjiakou, China; Zigong, China; Beijing, China; Ganzhou, China; Ningbo, Guangzhou, China; Gyeonggi-do, South Korea; and Istanbul, Turkey, found a statistically significant positive relationship between PM 2.5 , PM 10 , and COPD morbidity [13][14][15][16][17][18][19][20][21]. A recent systematic review, comprising 19 timeseries studies from around the globe, also estimated that the same PM 2.5 increase would result in a 1.60 percent increase in COPD admissions [22].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, our findings for particulate matter do not align with several previous reports in the literature that have been conducted in some other regional countries or cities [13][14][15][16][17][18][19]. We observed that short-term exposure to PM 2.5 or PM 10 did not correlate significantly with COPD morbidity, which was consistent with findings from Berlin, Germany, and Jinan, China, the authors of the above two articles identified that PM 2.5 and PM 10 were also not found to significantly influence COPD hospitalizations in their study [12,20], while the results of some prior studies in Zhangjiakou, China; Zigong, China; Beijing, China; Ganzhou, China; Ningbo, Guangzhou, China; Gyeonggi-do, South Korea; and Istanbul, Turkey, found a statistically significant positive relationship between PM 2.5 , PM 10 , and COPD morbidity [13][14][15][16][17][18][19][20][21]. A recent systematic review, comprising 19 timeseries studies from around the globe, also estimated that the same PM 2.5 increase would result in a 1.60 percent increase in COPD admissions [22].…”
Section: Discussioncontrasting
confidence: 99%
“…Two other timeseries analyses conducted in Ningbo and Jinan, respectively, found no statistically notable correlation between O 3 exposure and COPD admissions [12,14]. However, the findings of a few other studies were not in agreement with the results of this investigation, and there was a positive association between O 3 and COPD admissions [15][16][17]. One reason for the differences in the study data could be that ozone (O 3 ) production mechanisms are complex.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations